2020
DOI: 10.1148/ryct.2020200464
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Utilization and Outcomes in Vulnerable Populations during COVID-19 in New York City

Abstract: Background Coronavirus disease 2019 (COVID-19) affects vulnerable populations (VP) adversely. Purpose To evaluate overall imaging utilization in vulnerable subgroups (elderly, racial/ethnic minorities, socioeconomic status [SES] disadvantage) and determine if a particular subgroup has worse outcomes from COVID-19. Materials/Methods Of 4110 patients who underwent COVID-19 testing from March 3-April 4, 2020 at NewYork-Presbyterian Hospital (NYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…These findings are especially significant given that outside of the hospital, Hispanic patients are disproportionately affected by COVID-19. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are especially significant given that outside of the hospital, Hispanic patients are disproportionately affected by COVID-19. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 15 More recently, however, a study in a New York City healthcare system reported no disparity in image utilization in vulnerable subgroups with COVID-19 (elderly, racial/ethnic minorities, and socioeconomic underprivileged) as compared to their counterparts when given access to inpatient medical care. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The details of the study population and design were previously reported. 32 In brief, as shown in Fig. 1, we excluded patients with RT-PCR test results that were negative, indeterminate or invalid (n = 1563), those whose medical records were unavailable for review (n = 1417; 1392 from other NYP Hospitals to which EMR access was inaccessible, 25 restricted healthcare workers), and pediatric cases (n = 9).…”
Section: Study Design and Patientsmentioning
confidence: 99%